THE WORKING EXPERIENCE OF ZAO "WORKS TOCHLIT" - V. A. Patrusheva; V. M. Rudakov; N. N. Kiseleva; V. V. Velmisov (Литьë и металлургия)
It is shown that the results of investigations of steel and cast iron modifying prove the high efficiency of silicon-free complex ligature of type AKTse and its modifications, what allows to recommend it for out-of-furnace processing